A proposal for a classification of neuropathies according to their axonal transport abnormalities. Issue 9 (September 1986) - Jakobsen, J; Sidenius, P; Braendgaard, H
Abstract : Recent studies on axonal transport in experimental neuropathy are reviewed and the following combinations of pathological changes and underlying axonal transport abnormalities are proposed for a classification of polyneuropathies. Alterations of the anterograde transport of slow component a(SCa) leads to changes of the dimensions of the axon calibre without the occurrence either of overt neuropathy or fibre loss. Thus damming of SCa in beta, beta'-iminodiproprionitrile (IDPN) intoxication results in axonal swelling in nerve roots whereas decrease of SCa leads to atrophy distal to the swellings in IDPN intoxication and in streptozotocin induced diabetes as well. Decrease in the amount of material conveyed within the anterograde fast component (aFC) leads to acute axonal degeneration including break down of axons and fibre loss. This state occurs in acute hypoglycaemia and in doxorubicin intoxication. The most frequent type of polyneuropathy, namely distal axonopathy with accumulation of axon organelles leading to distal fibre loss, is associated with decrease in amount of the retrograde fast component (rFC). The transport is impaired before the appearance of symptoms and electrophysiological signs of neuropathy develop in the intoxications induced by parabromophenylacetylurea, acrylamide and 2.5 hexanedione, and the severity of neuropathy is proportional to the rFC impairment.